Teachers With Special Needs. De-Psychiatrization of Children in Schools - Batstra, Laura; van Roy, A.C. Marieke; Thoutenhoofd, Ernst D. (Frontiers in Sociology, 2021)
Psychiatrization not only affects adults. Ever more children in Western countries are being diagnosed with a mental disorder of behavior, such as ADHD. Children may often be labelled with the best intentions, for example in order to be able to provide them with suitable care and guidance. However, this labelling can have exclusionary effects and often entails the consequence that important discussion about contextual factors that give rise to (the perception of) unwelcome behavior or academic underperformance rarely, if at all, takes place. In this article we contend that although children are of central concern to schools and the design of pupils’ education, it is important not to make pupils the sole owner of problems that arise. It is therefore high time that a far more critical normative stance towards inclusive education is taken, in which the presently widespread biomedical approach is met with a school community response that focuses not on the nature of individual disorders but on the special need for additional capacity that schools and teachers have in meeting (perceived) deviant behaviors and emotions and/or academic underperformance. We argue that teaching should not set out to remedy individual diagnoses, but that teachers should be supported to extend their professional competence to the benefit of all pupils.